Regional patterns and temporal evolution of ocean iron fertilization and CO2 drawdown during the last glacial termination - Lambert, Fabrice; Opazo, Natalia; Ridgwell, Andy; Winckler, Gisela; Lamy, Frank; Shaffer, Gary; Kohfeld, Karen; Ohgaito, Rumi; Albani, Samuel; Abe-Ouchi, Ayako (My University, 2021)
The last time Earth's climate experienced geologically rapid global warming was associated with the last glacial termination, when atmospheric CO2 concentrations rose from 180 ppmv during the Last Glacial Maximum (LGM, 26-19 kaBP) to similar to 260 ppmv by the early Holocene (12-8 kaBP). About one quarter of that difference is thought to be due to a stronger biological pump during glacial times, driven by increased aeolian dust deposition and hence greater iron availability in ocean surface waters. However, dust supply did not change uniformly or in synchrony over the deglacial transition and what is not known is the relative importance of different oceanic regions and how this may have changed in time. Using an Earth system model of intermediate complexity, we quantify the sensitivity of atmospheric CO2 to regional changes in iron supply, and test six different global dust reconstructions in order to explore uncertainty in past dust changes. We confirm the Southern Ocean (>34 degrees S) as the region most sensitive to iron fertilization, with the Atlantic and Pacific sectors accounting for about 41 +/- 23% and 16 +/- 10%, respectively, of the total CO2 reduction from global iron fertilization. However, the North Pacific contributes 28 +/- 3% to the total implying an important role for Northern Hemisphere processes in driving deglacial CO2 rise. In addition, our analysis reveals an unexpected regional-temporal disparity, and while Southern Hemisphere iron fertilization influences atmospheric CO2 relatively constantly throughout the termination the impact of the Northern Hemisphere only occurs during the later stages of the termination. (C) 2020 The Author(s). Published by Elsevier B.V.
Keywords: co2; dust; iron fertilization; paleoclimate; termination